Faktor yang Berhubungan dengan Lama Rawat Inap Pasien Demam Berdarah Dengue di Rumah Sakit Islam Nahdlatul Ulama Demak - Safi’i, Akhmad; Rohmah, Solikhatur; Asumta, Muhammad Zulfikar; Aziz, Abdul; Hasyim, Masruroh; Khusniyah, Zulfa; Rajin, Mukhamad (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2026)
Dengue Hemorrhagic Fever (DHF) is an acute infectious disease that often requires hospitalization with a variable length of stay (LOS). Several factors have been shown to influence LOS; however, findings from previous studies conducted in different hospitals remain inconsistent. This study aimed to analyze the association between age, gender, platelet count, hematocrit level, and leukocyte count with LOS among patients with DHF at Nahdlatul Ulama Islamic Hospital (RSI NU) Demak. This study employed a cross-sectional design using medical record data from 64 hospitalized patients with DHF admitted between January and May 2025, selected through purposive sampling. The sample eligibility criteria included inclusion and exclusion criteria. The inclusion criteria were patients diagnosed with DHF (ICD-10: A90) who were hospitalized for ≥24 hours and had complete medical records. The exclusion criteria were patients with severe comorbidities or incomplete medical records. Data were analyzed using Spearman’s correlation test, which demonstrated a significant association between platelet count and LOS (rₛ = -0.322; 95% CI [-0.522; -0.080]; p-value = 0.009). The negative correlation coefficient indicates that an increase in platelet count was associated with a shorter LOS, although the strength of the association was weak. These findings indicate that platelet count plays an important role in determining the length of hospital stay among patients with DHF. Early monitoring of platelet count is important for supporting prognosis assessment and guiding therapeutic decision-making.